A promising impact of oral administration of noscapine against imiquimod-induced psoriasis-like skin lesions - Fahimeh Nourbakhsh; Seyed Hadi Mousavi; Pouria Rahmanian-Devin; Vafa Baradaran Rahimi; Hassan Rakhshandeh; Vahid Reza Askari (Mashhad University of Medical Sciences, 2023)
Objective: Psoriasis is a chronic inflammatory autoimmune disease. The effectiveness of noscapine has been employed as a helpful treatment for various disorders and subjected to recent theoretical breakthroughs.Materials and Methods: Psoriasis-like lesions were induced by topical application of 5% imiquimod (IMQ) (10 mg/cm2 of skin) in male Balb/c mice and then medicated with a single oral dose of methotrexate (MET) as a positive control or daily oral treatment of noscapine (5, 15 and 45 mg/kg). In this way, skin inflammation intensity, psoriatic itchiness, psoriasis area severity index (PASI) score, ear length, thickness, and organ weight were daily measured. At the end of the study, histological and immunohistochemical and enzyme-linked immunosorbent assays (ELISA, for pro-/anti-inflammatory factors) were performed in each ear.Results: IMQ caused psoriasis-like lesions. Noscapine markedly alleviated macroscopic parameters, namely ear thickness, ear length, skin inflammation, itching, and organ weight, as well as microscopic parameters including, pathology and Ki67 and p53, and tissue immunological mediators, such as tumour necrosis factor (TNF-α), interleukin (IL)-10, transforming growth factor (TGF-β), interferon-g (IFN-g), IL-6, IL-17, and IL-23p19 in the psoriatic skin in a concentration manner (p<0.05-<0.001).Conclusion: Therefore, noscapine with good pharmacological properties has considerable effects on psoriasis inflammation.